Black Mirror: el mismo storytelling para las fábulas del mañana - Nieri Rojas, César Ricardo (2021)
The way of telling stories in the audiovisual field has been transformed in recent years. The objective of this work is to explore whether the Black Mirror series respects the same conventions and narrative schemes that belong to the structure of the three acts. Likewise, analyze what is the percentage of time that is dedicated to each of the three acts in this audiovisual product. In order to resolve these questions, a narrative analysis tool has been designed that represents a valuable instrument for future research related to this.